Longitudinal Dispersion of Pollutants in Natural Streams - The Aggregated Dead-Zone Approach - Hassan, Mohd Nasir (Universiti Putra Malaysia Press, 1993)
The Aggregated Dead-Zone (ADZ) model provides a simple dynamic description of pollutant transportation and dispersion in a non-tidal river system and is an alternative to the well-known but more complicated advection-dispersion model. This paper presents the results obtained from the application of the model in a river system. The study shows the general form of functional relationships between the second order ADZ model parameters and stream discharge. In addition, more conventional hydrological analysis has yielded valuable information about the hydraulic characteristics of the reaches and has allowed for useful comparisons between these and the ADZ model parameters